2017
DOI: 10.1371/journal.pone.0169464
|View full text |Cite
|
Sign up to set email alerts
|

Can the Immune System Perform a t-Test?

Abstract: The self-nonself discrimination hypothesis remains a landmark concept in immunology. It proposes that tolerance breaks down in the presence of nonself antigens. In strike contrast, in statistics, occurrence of nonself elements in a sample (i.e., outliers) is not obligatory to violate the null hypothesis. Very often, what is crucial is the combination of (self) elements in a sample. The two views on how to detect a change seem challengingly different and it could seem difficult to conceive how immunological cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Following our previous work [43], it will be assumed that each agent can only perceive a binary signal, b , from the information displayed by agents of the opposite type. This simplifies considerably ILists and their orderings.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following our previous work [43], it will be assumed that each agent can only perceive a binary signal, b , from the information displayed by agents of the opposite type. This simplifies considerably ILists and their orderings.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve accurate anomaly detection, cellular frustrated systems (CFSs) must first undergo a training stage (also called repertoire education) during which detector ILists are changed to increasingly frustrate the overall dynamics and reach a maximally frustrated state. To understand how this guarantees accurate anomaly detection, it is important to take into consideration the mechanisms involved, thoroughly discussed in [3] and [43]. So far it has been found that CFSs can detect 3 types of anomalous patterns: 1) the presence of outliers, i.e., signals never (or rarely) displayed during training; 2) the absence of an abnormally large number of frequently displayed signals (as compared to what is observed during training); 3) the absence of combinations of signals frequently displayed during training.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations